Constitutive modeling of evolving plasticity in high strength steel sheets - Cai, Zhengyang; Diao, Keshan; Wu, Xiangdong; Wan, Min (International journal of mechanical sciences, 2016)
In this paper, biaxial tensile tests with cruciform specimens were conducted to obtain the experimental plastic work contours of DP590, DP780 and DP980 sheets. It was found that for high strength dual phase steel sheets, the outlines of the experimental work contours in the first quadrant evolve evidently with the increase of plastic dissipation. In order to calibrate the evolving isotropic and anisotropic plastic behaviors simultaneously, the Yld2000-2d yield criterion with variable exponent and coefficients (Yld2000-2d-Var) was introduced. In this model, the exponent m and coefficients αi of the Yld2000-2d was assumed as the function of the equivalent plastic strain. The identification procedures of the introduced parameters were then proposed based on minimizing the difference between the experimental and the model predicted yield points, using Levenberg–Marquardt optimization method. Afterwards, the proposed model was implemented into ABAQUS as user subroutine VUMAT with semi-implicit back-Euler integration algorithm. The numerical simulations of hydro-bulging and cylindrical deep drawing tests were then carried out to verify the validity of the proposed model. The results showed that the proposed model could enhance the predicting accuracy in both tests due to its flexibility. •The plasticity of the DP steel sheets evolves during the plastic deformation.•Yld2000-2d yield function with variable exponent for plasticity evolution.•The model improved the predicting precision of earing profile for DP steel sheets.